PENGARUH GREEN AWARENESS, GREEN PACKAGING TERHADAP MINAT BELI GREEN PRODUCT (Jurnal Riset Manajemen dan Akuntansi, 2022)
Tested in this study, the influence of green awareness and green packaging on the interest in buying green products. The research approach is in the form of quantitative associatives. The data collection was obtained from 100 respondents through an online survey. The determination of the respondent sample was taken through simple random sampling which included probability sampling techniques, with the determination of the sample size in an unknown population using the Cochran formula. The people of Jakarta, Bogor, Depok, Tangerang, and Bekasi (Jabodetabek) were the targets of research that was determined to be consumers of Aqua gallons of Bottled Drinking Water (AMDK) at least once. Data is collected through the distribution of online questionnaires using Google Forms. The research took place from February-September 2022 with a series of research in the form of scheduling, actualization (data collected, worked on, spelled out), and the formation of reports. The hypothesis was tested with a simple linear regression analysis, along with a t-test and an R2 test. The study concluded that partially green awareness and green packaging did not significantly affect the interest in buying green products. The research was limited to the place of residence of respondents from Jabodetabek, both independent variables were only partially tested against dependent variables, and independent variables had a very low ability to describe dependent variables as evidenced by small R2 values.